A practical toxicity bioassay for vicine and convicine levels in faba bean (Vicia faba). (17th May 2018) - Getachew, Fitsum; Vandenberg, Albert; Smits, Judit
Abstract: BACKGROUND: Faba bean ( Vicia faba ) vicine and convicine (V–C) aglycones (divicine and isouramil respectively) provoke an acute hemolytic anemia called favism in individuals with a glucose‐6‐phosphate dehydrogenase (G6PD) enzyme defect in their red blood cells. Geneticists/plant breeders are working with faba bean to decrease V–C levels to improve public acceptance of this high‐protein pulse crop. Here, we present a fast and simple ex vivo in vitro bioassay for V–C toxicity testing of faba bean or faba bean food products. RESULTS: We have shown that 1, 3‐bis (2‐chloroethyl)‐1‐nitrosourea (BCNU)‐treated (i.e., sensitized) normal red blood cells, like G6PD‐defective blood, displayed (i) continuous glutathione (GSH) depletion with no regeneration as incubation time and the dose of aglycones increased, (ii) progressive accumulation of denatured hemoglobin products into high molecular weight (HMW) proteins with increased aglycone dose, (iii) both band 3 membrane proteins and hemichromes, in HMW protein aggregates. We have also demonstrated that sensitized red blood cells can effectively differentiate various levels of toxicity among faba bean varieties through the two hemolysis biomarkers: GSH depletion and HMW clumping. CONCLUSION: BCNU‐sensitized red blood cells provide an ideal model for favism blood, to assess and compare the toxicity of faba bean varieties and their food products. © 2018 Society of Chemical Industry